ANALISIS PEMBANGUNAN INSFRASTRUKTUR DAERAH TERHADAP PENDAPATAN ASLI DAERAH - Lilis Setyowati; Lukman Ary Himawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
The purpose of this study is to analyze the long-term and short-term between road infrastructure development, tourism infrastructure development, health infrastructure development, and trade infrastructure development to local revenue in Semarang City. The method used in determining the sample is cluster random sampling. The data is obtained from local revenue and infrastructure development expenditures for eight years, namely from 2012-2019. The results show that health infrastructure development and trade infrastructure development in the long and short term contribute more and affect local revenue. In contrast, road infrastructure development and tourism infrastructure development do not contribute and do not affect local revenue.